Peningkatan Pengetahuan dan Kesadaran Masyarakat Tentang Penyakit Asma di Gor Satria Purwokerto - Teja Muti, Refa; Suandika, Made; Farhan, M; Bintang Khaerunnisa, Masayu; Ardyani, Meyla Livia (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Asthma is a chronic respiratory disease characterized by airway inflammation and narrowing, which can lead to symptoms such as shortness of breath, coughing, and wheezing. Many people still lack adequate knowledge about asthma management and prevention. Method: This community service program was conducted at GOR Satria Purwokerto and involved elderly community members. The activity included free health checks (BMI, blood pressure, SpO₂, blood glucose), educational sessions on asthma (causes, symptoms, prevention, and proper inhaler technique), and a Q&A discussion. Result: The counseling activity positively contributed to improving community knowledge and awareness regarding asthma, especially among elderly participants. The interactive education session enhanced understanding through direct communication and participation. Conclusion: This activity demonstrated the importance of health education and preventive efforts for chronic diseases like asthma. Challenges such as limited health literacy were noted, but overall, the activity strengthened promotive and preventive roles of health students in the community.